2019
DOI: 10.18632/aging.101907
|View full text |Cite
|
Sign up to set email alerts
|

MiR-204 reduces cisplatin resistance in non-small cell lung cancer through suppression of the caveolin-1/AKT/Bad pathway

Abstract: Non-small cell lung cancer (NSCLC) is the most common and lethal human malignant tumor worldwide. Platinum-based chemotherapy is still the mainstay of treatment for NSCLC. However, long-term chemotherapy usually induces serious drug resistance in NSCLC cells. Accordingly, treatment strategies that reverse the resistance of NSCLC cells against platinum-based drugs may have considerable clinical value. In the present study, we observed significant upregulation of CAV-1 expression and a significant decrease of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…To further confirm and validate a link between miR204-5p expression and CAV-1 expression, we demonstrated that transfection of A549 and NCI-H460 cells with a specific miR204-5p inhibitor (prior to TL treatment) effectively repressed the TL-induced inhibitory effect on Cav-1 mRNA transcript expression ( Figure 5A). These findings are consistent with reports of Cav-1 being a target of miR204-5p [17,[41][42][43][44]. More specifically, our data substantiate very recent findings by Huang et al [44] that downregulation of miR-204 expression is responsible for CAV-1 overexpression in cisplatin-resistant A549 cells.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…To further confirm and validate a link between miR204-5p expression and CAV-1 expression, we demonstrated that transfection of A549 and NCI-H460 cells with a specific miR204-5p inhibitor (prior to TL treatment) effectively repressed the TL-induced inhibitory effect on Cav-1 mRNA transcript expression ( Figure 5A). These findings are consistent with reports of Cav-1 being a target of miR204-5p [17,[41][42][43][44]. More specifically, our data substantiate very recent findings by Huang et al [44] that downregulation of miR-204 expression is responsible for CAV-1 overexpression in cisplatin-resistant A549 cells.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are consistent with reports of Cav-1 being a target of miR204-5p [17,[41][42][43][44]. More specifically, our data substantiate very recent findings by Huang et al [44] that downregulation of miR-204 expression is responsible for CAV-1 overexpression in cisplatin-resistant A549 cells. Taken together, our findings indicate that: 1) Cav-1 is a likely target of miR204-5p and 2) miR204-5p plays a key role in TL-induced down-regulation of Cav-1/Sirt-1/-3 in A549 and NCI-H460 NSCLC cells.…”
Section: Discussionsupporting
confidence: 94%
“…MiRs are endogenous non-coding RNA, existed in eukaryotic cells to suppressed genes expression on the transcriptional level and play the part of cancer gene or antioncogene [9]. MiR-204 is ordinarily poorly expressed in multiple cancers, and pose as a tumor inhibitor in cancers [10]. It has been suggested that by regulating miR-204-3p and inhibiting autophagy, downregulated expression of lncRNA AK139328 alleviated myocardial I/R injury in glycuresis mice [11].…”
Section: Introductionmentioning
confidence: 99%
“…In A549 and PC-9 cells, Cav-1 expression can be negatively modulated by its upstream regulator miR-204. The phosphorylation of AKT and Bad can be further suppressed by the miR-204/Cav-1 pathway, which can promote cisplatin-induced apoptosis by silencing Bcl-2 and Bcl-xl, indicating the positive role of Cav-1 during this process [105]. In paclitaxel-resistant A549 cells, Cav-1 knockdown upregulates Bax, caspase-3 and caspase-9, and downregulates Bcl-2, finally prompting cell apoptosis [49].…”
Section: Roles Of Cav-1 In Programmed Cell Deathmentioning
confidence: 99%